Diseño del Sistema de Gestión de Inventarios para la Empresa Distribuidora Sensación de la Ciudad de Santa Marta - Magdalena (2022)
The present work is carried out showing a proposal for the design of the inventory management system for the company Distribuidora Sensación of the city of Santa Marta - Magdalena, being that she does not know the current methods and tools associated with it, to this are added the problems where the requirements given by the managerial guideline must be met. In itself, all this research focuses on the influence it has on the warehouse area, basically on the handling, management and availability of products; In the company Distribuidora Sensación, information was collected using strategies such as surveys and unstructured interviews. In turn, giving the technicians a growth in knowledge that is emerging in search of improvement in working conditions and stock management with product quality, under the ABC analysis and the Process Flowchart as a second measure, these served as support, thanks to their applicability within the warehouse process, clarifying doubts in some and in the end a Management Model of the total cost of the inventory policy was designed which would support the processes of the organization